COVID-19 Vaccine Perceived Risks and Benefits: Scale Development and Initial Tests of the Psychometric Properties. Issue 2 (4th March 2022) - Sachdeva, Ruchika
ABSTRACT: Background: COVID-19 pandemic has been a global health threat since December 2019. It has brought the world to a standstill. The development of a vaccine has sparked great hope among all the individuals across the globe. Purpose: This study aimed to measure the perceived risks and benefits associated with the COVID-19 vaccines and to develop a scale to measure the perceived risks and benefits associated with the COVID-19 vaccines. Method: This research closely follows the procedure for developing better measures given by Churchill. Psychometrics of the scale is tested with the help of data collected over two rounds of data collection. The analytical tools used are Cronbach's alpha, item to total correlation, and factor analysis. Results: Drawing on the previous literature and focus group, a five-dimensional scale of perceived risks and a four-dimensional scale of perceived benefits was developed finally. Discussion: This scale has desirable reliability and validity properties that could be used by aspiring researchers and health professionals for gauging the perception of an individual related to COVID-19 vaccines. Translation to Health Education Practice : This research provides a useful insight for health educators for generating and highlighting the various benefits associated with the vaccines.